Kutaisi City In "Greenstone 3.08" Collection - Kvirkelia, Ketevan; Chichinadze, Tamta; Kiladze, George (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
It’s not possible to imagine a modern society without education. Nowadays, one of the primary sources to get an education is school. A modern school of socalled information age couldn’t function without implementing digital technologies and electronic educational resources. Unfortunately, Georgian electronic educational resources can’t keep up with the standards of digital technologies worldwide. * Students of this so-called information age have special interest in getting information by means of digital formats. * The main source to get digital information is “Wikipedia” * Students at all three levels of the school give huge attention to get thorough information about the history, culture, present and especially the future of their home town. * Students at all grade levels of education get information about their home towns from relevant pages on “Wikipedia”. * Students think that information about different cities in the internet space, including the educational resources of the national library is not sufficient, although it enables you to learn quite a lot about them. As for their wishes, it would be a good idea to gather all the information on one portal, especially the full-text files. * The majority of respondents know their city on the average level. (Tbilisi is an exception: most of them have quite good knowledge of it) However, they are interested in its history, culture, present and especially future. The majority of respondents state that despite the interest they have insufficient information about their home-towns since they were not exposed to it in their young years and now they lack the time to learn it. * Most of the respondents consider that the main source of information is the Wikipedia page, but they think it needs to be expanded. * Most of the respondents think they would use the “Tbilisi city page” together with digital literature (books, articles) added to the Wikipedia data. * The Majority of respondents consider the National Parliamentary Library of Georgia has good online resources, but there is a need for more digital books and articles. * Most of the respondents state that schools should teach “Home-town” as a subject for one semester (one day per week, at the secondary level, 6-9 grades), it shouldn’t be a compulsory subject and should have a form of additional lesson.